Avaliação do PMAQ sob a ótica dos gestores municipais de saúde no interior do Rio Grande do Sul - Engel, Rosana Huppes (2015)
The health evaluation is understood to be a guideline for the effectiveness of public administration, seeking to ensure health access and care quality. Strategies have been undertaken by the National Primary Care Policy to stimulate the expansion of access to health services. Thus, in 2011, the National Program for Improving Access and Quality of Primary Care (PMAQ) was created by the Ministry of Health with actions to assess the results of the new health policy and extend the three levels of management capacity. This study aimed to analyze the understanding of the health evaluation and PMAQ implementation from the perspective of Municipal Health Managers of the 4th Regional Health District of Rio Grande do Sul. This is a qualitative, descriptive, exploratory study. The survey was conducted in the Region of Verdes Campos belonging to the 4th Regional Health Coordination of Rio Grande do Sul in the municipalities that joined PMAQ in its first cycle in 2011. Thus, the sample of participants was selected intentionally and included eight local health managers. Data collection took place from January to March 2014 through a semi-structured interview. Data analysis was based on the proposed content analysis by subject category of Minayo. The study followed the recommendations of Resolution No. 466 of 12 of the National Health Council. The data allowed the conclusion that, in the context of this study, municipal managers are predominantly male aged 40 50 years old, which is in line with other studies in the area. It was noted that participants did not conceptualize the health evaluation as they use the same monitoring routines as in the evaluation practice. Although PMAQ is the only systematic assessment experience considered by municipal managers, they show little ownership of it. It can be seen that managers are active in the four stages of program development but complained of limited access and difficulties in relation to external evaluation. The study contributes to the construction of nursing and health knowledge and proposes advances in the subject of health evaluation.